2020
DOI: 10.1111/hae.14230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fibrinogen concentrate for on‐demand treatment of bleeding and surgical prophylaxis in paediatric patients with congenital fibrinogen deficiency

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…23 Further studies dissecting the differential contributions on prothrombin conversion and thrombin decay showed that fibrinogen slowed down the inactivation of thrombin and that fibrinogen itself stimulated prothrombin conversion. 24 The fact that in vivo TG is increased is supported by the observation of elevated plasma levels of TAT complexes, which decrease after FC infusion 25 26 27 ; in our study however, we failed to show such a variation. The unexpected finding that at the same time TG is somewhat delayed (i.e., prolonged lag time after fibrinogen infusion) deserves further studies.…”
Section: Discussionmentioning
confidence: 48%
“…23 Further studies dissecting the differential contributions on prothrombin conversion and thrombin decay showed that fibrinogen slowed down the inactivation of thrombin and that fibrinogen itself stimulated prothrombin conversion. 24 The fact that in vivo TG is increased is supported by the observation of elevated plasma levels of TAT complexes, which decrease after FC infusion 25 26 27 ; in our study however, we failed to show such a variation. The unexpected finding that at the same time TG is somewhat delayed (i.e., prolonged lag time after fibrinogen infusion) deserves further studies.…”
Section: Discussionmentioning
confidence: 48%
“…Fibrinogen concentrate is used clinically to improve hemostasis in bleeding patients, based on studies that have demonstrated that there are associations between low plasma concentration of fibrinogen and increased bleeding volumes and transfusion requirements 3–5 . Supplementation with fibrinogen concentrates improves clot strength and is therefore used in patients with inherited and acquired hypofibrinogenemia 9–12,18,19 …”
Section: Discussionmentioning
confidence: 99%
“…FORMA‐02 (NCT02267226), performed in adults/adolescents (aged ≥12 years), 14 and FORMA‐04 (NCT02408484), performed in children (aged <12 years), 12 were multinational, multicenter, prospective, open‐label, uncontrolled Phase 3 studies to assess HFC efficacy and safety for the on‐demand treatment of bleeding episodes (BEs) and surgical prophylaxis in patients with CFD. Designs of these trials have been described previously 12,14 . Data presented herein are for all surgical patients included across these two studies.…”
Section: Methodsmentioning
confidence: 99%
“…All clinical efficacy assessments were adjudicated by an Independent Data Monitoring and Endpoint Adjudication Committee (IDMEAC). Overall hemostatic efficacy was assessed using a 2‐point scale: treatment success or failure 12,14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation